2014
DOI: 10.1073/pnas.1321930111
|View full text |Cite
|
Sign up to set email alerts
|

Transactivation of programmed ribosomal frameshifting by a viral protein

Abstract: Programmed −1 ribosomal frameshifting (−1 PRF) is a widely used translational mechanism facilitating the expression of two polypeptides from a single mRNA. Commonly, the ribosome interacts with an mRNA secondary structure that promotes −1 frameshifting on a homopolymeric slippery sequence. Recently, we described an unusual −2 frameshifting (−2 PRF) signal directing efficient expression of a transframe protein [nonstructural protein 2TF (nsp2TF)] of porcine reproductive and respiratory syndrome virus (PRRSV) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
185
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(195 citation statements)
references
References 67 publications
10
185
0
Order By: Relevance
“…Despite its crucial role in protein translation, ribosomal protein's involvement in RNA virus replication and dissemination has been well studied [38,39]. A few recently published reports demonstrated the versatility of ribosomal proteins in either facilitating or inhibiting viral growth during infection [40][41][42]. In addition, although ribosome has traditionally been thought to function as the catalytic machinery for translational elongation, Lee et al also showed that ribosomal subunit protein rpL40 acts as a requisite for vesicular stomatitis virus (VSV) capdependent translational regulation [43].…”
Section: Discussionmentioning
confidence: 99%
“…Despite its crucial role in protein translation, ribosomal protein's involvement in RNA virus replication and dissemination has been well studied [38,39]. A few recently published reports demonstrated the versatility of ribosomal proteins in either facilitating or inhibiting viral growth during infection [40][41][42]. In addition, although ribosome has traditionally been thought to function as the catalytic machinery for translational elongation, Lee et al also showed that ribosomal subunit protein rpL40 acts as a requisite for vesicular stomatitis virus (VSV) capdependent translational regulation [43].…”
Section: Discussionmentioning
confidence: 99%
“…The sequence GGUUUUU at the exact frame-shifting site and the downstream conserved motif CCCANCUCC were shown to be required for generating this À 2 PRF product. A follow-up study (Li et al, 2014) further demonstrated that PRRSV Nsp1β is also required for the efficient ribosome frameshifting as a trans-activator protein in Nsp2TF expression. In addition to À 2 PRF, À 1 PRF can also occur at the same site with a much lower efficiency, generating À 1 PRF product Nsp2N.…”
Section: Loss Of Nsp2tf Expression By Mutant Prrsvsmentioning
confidence: 97%
“…GP, glycoprotein; M, membrane; E, envelope; N, nucleocapsid. Unlike EAV, the genomes of PRRSV and other arteriviruses contain an alternative transframe (TF) ORF underlying the non-structural protein 2 (nsp2)-coding region, which is expressed by −2 ribosomal frameshifting (yielding nsp2TF; Fang et al, 2012), whereas a −1 ribosomal frameshift at the same position yields a third, truncated nsp2 variant (nsp2N; Li et al, 2014). The positions corresponding to (known or predicted) polyprotein cleavage sites are depicted above the replicase ORFs; red arrowheads, sites cleaved by the nsp4 serine protease (S); blue arrowheads, sites cleaved by papain-like proteases (P) in the nsp1-nsp2 region.…”
Section: Introductionmentioning
confidence: 99%